Locating Hell in Islamic traditions - Lange, Christian. (Islamic History and Civilization, 2015)
Islam is often seen as a religious tradition in which hell does not play a particularly prominent role. This volume challenges this hackneyed view. Locating Hell in Islamic Traditions is the first book-length analytic study of the Muslim hell. It maps out a broad spectrum of Islamic attitudes toward hell, from the Quranic vision(s) of hell to the pious cultivation of the fear of the afterlife, theological speculations, metaphorical and psychological understandings, and the modern transformations of hell. Contributors: Frederick Colby, Daniel de Smet, Christiane Gruber, Jon Hoover, Mohammad Hassan Khalil, Christian Lange, Christopher Melchert, Simon O'Meara, Samuela Pagani, Tommaso Tesei, Roberto Tottoli, Wim Raven, and Richard van Leeuwen.